Symbiotic cardiac pacemaker - Han Ouyang (Nature Portfolio, 2019)
Implantable medical electronic devices are limited by battery lifetime and inflexibility, but self-powered devices can harvest biomechanical energy. Here the authors demonstrate cardiac pacing and correction of sinus arrhythmia with a symbiotic cardiac pacemaker, which is an implanted self-powered pacing system powered by cardiac motion, in a swine.